2021
DOI: 10.1002/ppul.25692
|View full text |Cite
|
Sign up to set email alerts
|

How do Cormic Index profiles contribute to differences in spirometry values between White and First Nations Australian children?

Abstract: Background: Spirometry values of First Nations Australian children are lower than White children. One explanation relates to differences in the sitting-height/ standing-height ratio (Cormic Index), as this accounts for up to half the observed differences in spirometry values between White children and other ethnicities. We investigated whether the Cormic Index of First Nations children differs from White children and if this explains the lower spirometry values of First Nations children. Methods: First Nations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…We found that the age‐related decline in FEV 1 and FVC values is overestimated in this population when using the GLI‐2012 other/mixed equation; the influence of height on FEV 1 and FVC values was also overestimated by the GLI‐2012 other/mixed equation, but not the race‐neutral GLI‐2022 global reference equation. We have previously reported that the body proportions of First Nations children are different to those of children who participated in the Third National Health and Nutrition Examination Survey; for example, sitting height comprises a smaller proportion of standing height 21 …”
Section: Discussionmentioning
confidence: 99%
“…We found that the age‐related decline in FEV 1 and FVC values is overestimated in this population when using the GLI‐2012 other/mixed equation; the influence of height on FEV 1 and FVC values was also overestimated by the GLI‐2012 other/mixed equation, but not the race‐neutral GLI‐2022 global reference equation. We have previously reported that the body proportions of First Nations children are different to those of children who participated in the Third National Health and Nutrition Examination Survey; for example, sitting height comprises a smaller proportion of standing height 21 …”
Section: Discussionmentioning
confidence: 99%
“…A further consideration of our cross-sectional study was that we Finally, borderline low spirometry findings may well have been normal if adjusted for the lower Cormic Index observed in Aboriginal children. 27 However, the presence of a respiratory physician on the study team facilitated interpretation of results, for example, where a borderline restrictive spirometry curve was found in the absence of abnormal symptoms or physical findings children were classified as healthy.…”
Section: Discussionmentioning
confidence: 99%
“…Collaro et al 47 The mean FVC, FEV 1 , and forced expiratory flow between 25% and 75% of FVC (FEF 25-75 ) fit the predicted value based on GLI reference equation for Northeast Asians. However, the observed variance was slightly greater than the predicted, resulting in a high lower limit of normal and possible overdiagnosis of lung function impairment.…”
Section: Reference Equationsmentioning
confidence: 93%
“…Collaro et al 47 evaluated whether differences in body proportions could explain lower spirometry values in First Nations Australian children compared with Caucasians. They found that the Cormic index (the ratio of sitting height to standing height) was significantly higher in White children as compared to First Nations children.…”
Section: Introductionmentioning
confidence: 99%